Wybrane aspekty ewolucji prozy kobiet — dwa pokolenia - Martyna Kowalska (Rusycystyczne Studia Literaturoznawcze, 2020)
This article aims to present the evolution of the literary approach to womanhood which took place in the prose of women writers in Russia over the course of two decades (the 1990s of the twentieth century through the 2000s of the twenty-first century). The so-called ‘Mother Generation’ of the nineties (the New Amazons Group, Lyudmila Ulitskaya, Lyudmila Petrushevskaya), which appeared in literature during the decline of the Soviet Union, developed previously unknown strategies for the representation of womanhood, with a focus on the repressed female subject, a distinct conception of victimhood, mutilated corporeality, and the search for self-identity. The ‘Daughter Generation’ (Ekaterina Sadur, Irina Denezhkina), whose first works appeared in the early twenty-first century, broke with the traditional representation of womanhood as trauma. Instead of describing the pain of female existence, these writers adopted the language of ‘the lost generation’, as if suspended in a vacuum between the Soviet era and the age of transformation.